Use of Electronic Medical Records System to Enforce Adherence to Maternal and Infant Health Treatment Protocol in Malawi: A Pilot Case Study at at Bwaila Maternity Hospital - Khomani, Patricia; Mputeni, Chimwemwe; Gadabu, Oliver (My University, 2013)
Technology continues to present opportunities of being used in different settings to meet information needs. Healthcare has been an emerging area in which this need has manifested itself with several initiatives being carried out in resource constrained settings. This paper describes the design, development and implementation of an electronic medical record system in a busy ante-natal and maternity clinic in Sub-Saharan Africa in Malawi. The development of the EMR follows agile paradigm with the Heeks reality gap model to improve the features in the system. The system has now been deployed at the Bwaila maternity wing and has recorded over 6,400 deliveries since April 2013. The system has embedded ante-natal and maternal protocols and presents an opportunity to improve care outcomes.
Keywords: Maternal health; treatment protocols; Electronic Medical Record Systems; Point of Care